Toxoplasma gondii harbors a hypoxia-responsive coproporphyrinogen dehydrogenase-like protein - Melanie Key; Carlos Gustavo Baptista; Amy Bergmann; Katherine Floyd; Ira J. Blader; Zhicheng Dou (mSphere, 2024)
ABSTRACTToxoplasma gondii is an apicomplexan parasite that is the cause of toxoplasmosis, a potentially lethal disease for immunocompromised individuals. During in vivo infection, the parasites encounter various growth environments, such as hypoxia. Therefore, the metabolic enzymes in the parasites must adapt to such changes to fulfill their nutritional requirements. Toxoplasma can de novo biosynthesize some nutrients, such as heme. The parasites heavily rely on their own heme production for intracellular survival. Notably, the antepenultimate step within this pathway is facilitated by coproporphyrinogen III oxidase (CPOX), which employs oxygen to convert coproporphyrinogen III to protoporphyrinogen IX through oxidative decarboxylation. Conversely, some bacteria can accomplish this conversion independently of oxygen through coproporphyrinogen dehydrogenase (CPDH). Genome analysis found a CPDH ortholog in Toxoplasma. The mutant Toxoplasma lacking CPOX displays significantly reduced growth, implying that T. gondii CPDH (TgCPDH) potentially functions as an alternative enzyme to perform the same reaction as CPOX under low-oxygen conditions. In this study, we demonstrated that TgCPDH exhibits CPDH activity by complementing it in a heme synthesis-deficient Salmonella mutant. Additionally, we observed an increase in TgCPDH expression in Toxoplasma when it grew under hypoxic conditions. However, deleting TgCPDH in both wild-type and heme-deficient parasites did not alter their intracellular growth under both ambient and low-oxygen conditions. This research marks the first report of a CPDH-like protein in eukaryotic cells. Although TgCPDH responds to hypoxic conditions and possesses enzymatic activity, our findings revealed that it does not directly affect acute Toxoplasma infections in vitro and in vivo.IMPORTANCEToxoplasma gondii is a ubiquitous parasite capable of infecting a wide range of warm-blooded hosts, including humans. During its life cycle, these parasites must adapt to varying environmental conditions, including situations with low-oxygen levels, such as intestine and spleen tissues. Our research, in conjunction with studies conducted by other laboratories, has revealed that Toxoplasma primarily relies on its own heme production during acute infections. Intriguingly, in addition to this classical heme biosynthetic pathway, the parasites encode a putative oxygen-independent coproporphyrinogen dehydrogenase (CPDH), suggesting its potential contribution to heme production under varying oxygen conditions, a feature typically observed in simpler organisms like bacteria. Notably, so far, CPDH has only been identified in some bacteria for heme biosynthesis. Our study discovered that Toxoplasma harbors a functional enzyme displaying CPDH activity, which alters its expression in the parasites when they face fluctuating oxygen levels in their surroundings.